Infectious Keratitis: Secreted Bacterial Proteins That Mediate Corneal Damage - Mary E. Marquart; Richard J. O'Callaghan (Journal of Ophthalmology)
Ocular bacterial infections are universally treated with antibiotics, which can eliminate the organism but cannot reverse the damage caused by bacterial products already present. The three very common causes of bacterial keratitis—Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pneumoniae—all produce proteins that directly or indirectly cause damage to the cornea that can result in reduced vision despite antibiotic treatment. Most, but not all, of these proteins are secreted toxins and enzymes that mediate host cell death, degradation of stromal collagen, cleavage of host cell surface molecules, or induction of a damaging inflammatory response. Studies of these bacterial pathogens have determined the proteins of interest that could be targets for future therapeutic options for decreasing corneal damage.